Analysis of Intermittent Electrical Shutdown Electrostatic Precipitator Method in Enhancing Energy Efficiency - Ilham, Muhammad Farras; Zulthoni, Yahya; Riantono, Kris (Journal of Mechanical Design and Testing, 2025)
The Electrostatic Precipitator (ESP) is a critical component in Coal-Fired Power Plants, responsible for capturing fine dust particles from the exhaust gases produced during coal combustion. The ESP operates by using electrically charged electrodes to attract dust particles; however, dislodging the dust adhered to these electrodes can be challenging, even with the use of Hammer Rapping. A novel method known as Intermittent Shutdown ESP (IES) involves periodically turning off the electrical charge on the electrodes, making it easier for the adhered dust to be released from the electrode plates. This theoretical study aims to analyze the potential benefits of the Intermittent Shutdown ESP method in improving energy efficiency and dust removal performance. The research focuses on calculating energy consumption in the operation of the ESP and comparing the performance of ESP with and without the IES method. Utilizing a quantitative approach, this study models the performance of ESP and analyzes energy consumption data, primarily focusing on the rectifier transformers while excluding contributions from hopper heaters, box heaters, and rappers. The findings reveal that the IES method significantly reduces energy consumption, achieving savings of approximately 44.1 kWh per operational cycle, with monthly and annual energy savings of 31.717,5 kWh and 380.610 kWh, respectively. This translates to substantial cost reductions, with potential monthly savings of Rp 53,3 million and annual savings of Rp 640 million. The IES method also enhances the overall efficiency and reliability of ESP systems by reducing the energy load across all fields. In conclusion, the IES method presents a viable and cost- effective strategy for optimizing ESP operations, contributing to both energy efficiency and cost savings in Coal-Fired Power Plants.